INVESTIGATION OF EFFECTIVENESS OF WAKE EQUALIZING DUCT FOR A CHEMICAL TANKER - Celik, Fahri; Ekinci, Serkan (YILDIZ TECHNICAL UNIV, 2010)
In this study, effect of the wake equalizing duct (WED) on the propulsion performance of a chemical tanker is investigated numerically. Computations are performed by using a commercial computational fluid dynamics code based on finite volume method. Total 56 runs are achieved for several WED geometries and locations at various speeds of ship. It can be concluded from this study that propeller characteristics and resistance of the ship are affected slightly by the presence of the WED, but propulsive efficiency of the ship is improved about 10 % with generated an additional thrust. Consequently, it can be provided substantially fuel saving for ships owing to well designing WED.
Keywords: Wake equalizing duct; CFD; propeller; propulsion; Engineering